Renal Artery Stenosis Presenting with Resistant Hypertension in Children and Adolescents: A Report of Five Cases - BALTACIOĞLU, FEYYAZ; ALPAY, HARİKA; GÖKCE, İBRAHİM; SAK, MEHTAP; YILDIZ, NURDAN (AVES, 2020)
We aimed to present five patients presenting with hypertension and diagnosed as renal artery stenosis. Five patients with renal artery stenosis were studied retrospectively. Two of our cases were diagnosed as fibromuscular dysplasia, other cases were diagnosed as Takayasu arteritis and Moyamoya disease, and one of them had congenital vascular abnormality. Renovascular hypertension is one of the most important causes of secondary hypertension in children, and renal artery stenosis constitutes a significant proportion of renovascular disease. We must consider renal artery stenosis in children presenting with resistant hypertension.
Keywords: Children; hypertension; renal artery stenosis; TAKAYASU ARTERITIS